The Training of the Twelve - Alexander Balmain Bruce; Olan Hendrix (intro.); D. Stuart Briscoe (Michigan Kregel Publications, 1988)
The lessons and patterns in ageless management principles employed by our Lord with His disciples are an inspiring model for those who seek greater depth and stability in the Christian church today. Featured in this classic work is Christ, the Master Potter, molding and fashioning His disciples into useful vessels. The Training of the Twelve is rich in thoughts, not only for preacher and teacher, but it is also invaluable for every Christian who is interested in being a leader or in preparing others to lead. - Back cover.
Reprint. Originally published: 4th ed., rev. and improved. New York : A.C. Armstrong and Son, 1894.
Keywords: Biblical Studies (3ebOeGJ hOQGSGJ GdcJGH GdebOSs; Bible